Preferences, Acceptability and Usage of Mobile Health Applications Among Undergraduate Nursing Students: A Multisite, Cross-Sectional Survey - Ramya Kundayi Ravi RN, MSc, PhD; Priya Baby RN, MSc, PhD; Bharat Pareek RN, MSc, PhD; Jisa George T RN, MSc, PhD; Mona Gamal Mohamed RN, MSc, PhD; Sirwan Khalid Ahmed RN, MSc (SAGE Publishing, 2024)
Introduction and objective Mobile health applications (mHealth) can bring revolutionary changes to health care by making it more accessible, cost-effective, and efficient. The successful adoption of mHealth is largely determined by its acceptance by providers and end users. The acceptance of mHealth among nursing students, who are the future nurses, needs to be understood. This study aimed to determine the preferences, acceptability, and usage of mHealth applications among undergraduate nursing students. Methods A descriptive cross-sectional study was conducted in two selected universities in southern and northern India. A convenience sample of 567 undergraduate nursing students was recruited for the study. The data were collected using a structured questionnaire via Google Forms. Results mHealth applications were presently used by 32.9% of the students. The most common types of mHealth applications used were diet related (27.6%) and lifestyle related (23.4%). The majority of nursing students were willing to use mobile phones for consulting health professionals (78.8%) for prevention and management of health and disease. (83.1%), and for emergencies (73.3%). While more than half of the students were willing to recommend mHealth applications for patients, those students who were using two or more mHealth apps were more likely to recommend the same for the patients. Conclusion The results of the study highlight about the usage of mobile health applications among the nursing students. The students consider mHealth applications to be useful for delivering health-related services to end users. The study underscores the need to sensitize students about the possible usage of mHealth in healthcare delivery.